Effect of Cu, Cr, S Doped TiO2 for Transparent Plastic Bar Reinforced Concrete - Seung-Hoon Seo; Byoung-Il Kim (Applied Sciences, 2020)
In this study, after firing and powdering Cu, Cr, and S with NP-400 TiO2, an NOx removal rate test was performed according to the ISO test method to analyze the photocatalytic reactivity in visible light. The distribution of the photocatalyst and visible light reactivity on the surface of the test specimen were confirmed through SEM (Scanning electron microscope), EDS (Energy dispersive spectroscopy), XRD (X-ray diffraction), UV-visible absorption spectrum and energy band gap tests. The flowability of UHPC (Ultra high performance concrete) slightly decreased due to the increase in the photocatalyst mixing rate, but both J-Ring and L-Box test results showed that there is no problem when concrete is placed. As a result of SEM and EDS tests, good microstructure and peak values were confirmed in the test specimens doped with Cu, and as a result of the XRD test, anatase and rutile peaks were confirmed in the Cu, Cr, and S specimens. In the UV-visible absorption spectrum analysis, it was confirmed that only the specimen doped with Cu maintains a high absorption power of 0.8 up to 700 nm, and the inherent band gaps are reduced to 2.9 eV, thereby increasing the possibility of reaction in visible light. Finally, as a result of the NOx removal test by the ISO test method, about 15.8% was removed for 5 h in the specimen doped with Cu, and the removal efficiency is estimated to be possible up to about 25% when applied with the TPBRC (transparent plastic bar reinforced concrete).